Developing operational risk-level assessment for selecting auditable units: Factor analysis and analytic hierarchy process approach - Dewantoro, Fuad Ramdhan; Lestari, Yetty Dwi (Badan Pemeriksa Keuangan Republik Indonesia, 2025)
This study introduces a new method for calculating operational risk levels in selecting audit units at Statistics Indonesia (BPS). The key novelty of this study lies in its two-level assessment framework, which systematically compares different risk calculation methods to determine the most effective approach for operational risk evaluation. Using exploratory factor analysis, the study identifies four key operational risk factors: operational costs, internal control, investment and guarantees, also financial performance. The analytic hierarchy process (AHP) is then applied to systematically assign weight scores to these factors and their corresponding subcriteria based on expert judgment. Integrating these approaches results in a more structured, comprehensive, and accurate risk assessment model. Compared to the previous method, this new method exhibits a narrower but more optimal risk-level range, a slightly higher average operational risk level, and fewer instances of underestimation or overestimation. This new method enhances the precision of risk assessment in selecting BPS audit units, enabling the internal audit team to allocate resources more effectively by prioritizing high-risk work units. Consequently, the overall efficiency and effectiveness of BPS's internal audit process improved.